La IA como recurso didáctico para el desarrollo de la destreza escritural - Bastidas Chicaiza, Marlon Bernabe (2025)
The objective of this research work is to analyze the effectiveness of AI as a didactic resource for the development of writing skills in students of the second level of high school “D” at U. E. Juan de Velasco in the 2024-2025 school year. For this purpose, a quantitative methodology with a pre-experimental design and a descriptive scope has been used, since the process during the intervention is detailed, as are the results obtained at the beginning and after applying an evaluation rubric, which serves as the instrument of the study. These results were compiled through an academic test (diagnostic test), showing that, at first, the students present deficient writing skills in both grammatical and linguistic aspects, as well as in argumentation, reflection, and criticism. Then, with the same errors detected in the diagnostic test, a treatment intervention was carried out using AI-generated activities, all this together with the constantly assisted pedagogical support. As final results from the post-test indicate, significant progress was observed in the development of writing skills across all criteria, except spelling. In conclusion, AI as a didactic resource is effective for developing and advancing students' writing skills, provided it is used in a conscious, ethical, and responsible manner.